Effects of steam explosion pretreatment on the composition and biological activities of tartary buckwheat bran phenolics. Issue 5 (13th May 2020) - Li, Weizhou; Zhang, Xiaoli; He, Xiaoqin; Li, Fuhua; Zhao, Jichun; Yin, Ran; Ming, Jian
Abstract : Steam explosion (SE) is an efficient technology to disrupt materials for improving their quality. Abstract : Steam explosion (SE) is an efficient technology to disrupt materials for improving their quality. In this study, SE was applied to release phenolics and improve the roughening of tartary buckwheat bran. The results showed that SE promoted the dissolution of phenolics, particularly, the content of the bound fraction was nearly increased by two times (0.36 vs. 0.99 mg GAE per g DW). The analysis of the phenolic composition showed that SE improved the liberation of bound pyrogallic acid, protocatechuic acid and caffeic acid. The biological activity tests indicated that SE effectively enhanced the oxygen radical absorbance capacity (ORAC) in vitro of the extract of bound phenolics by 270%. It also improved the cellular antioxidant activity (CAA) in vitro of the extract of free phenolics by 215%. Furthermore, SE showed potential in improving the antiproliferative activity of the total phenolic extract against Caco-2 cells as well as the bound phenolic extract against HepG2 cells in vitro .